Kemampulabaan PT. BPD Bali Pada Masa Pandemi Covid-19 - Nengah Sukendri; Ni Putu Ari Aryawati (Guna Sewaka, 2022)
This analysis aims to analyze the profitability of PT. BPD Bali during the Covid-19 Pandemic. This analysis uses a different test of quantitative research. The data source uses the financial statements of the PT. BPD Bali bank before and also data during the pandemic. Different test paired sample t test is used in this study using SPSS software tools. The results of the analysis explain that there is no difference before and during the COVID-19 pandemic in terms of the profitability of PT. BPD Bali. This means that the condition of profitability of PT. BPD Bali is classified as a healthy bank, judging by the analysis of the ROA ratio before and during the Covid-19 pandemic, where the ROA ability which was previously able to earn high profits experienced a not too large decrease so that sufficient profit could occur. higher than the assets it owns.